Implementasi Jaringan RT/RW Net menggunakan metode IP Binddings dan HTB untuk Usaha Menengah Kecil Mikro - Wildan Arif Hidayatulloh; Hamzah Setiawan; S Sumarno (LPPM STIKOM Tunas Bangsa, 2023)
The Internet is one of the results of technological advancement. Almost all activities can be done online using the Internet. However, the distribution of the Internet has not reached all sectors, especially in remote villages. This is due to the expensive cost of Internet installation, making it inaccessible to middle to lower-class communities. One solution to this problem is the RT RW Net business, which not only benefits the owner but also provides affordable Internet access to lower-middle-class communities. This research discusses the creation of RT RW Net using IP Bindings and HTB methods. IP Bindings is a technique of the hotspot server where the MAC Address of the user's Access Point is registered in the bypass type of IP Bindings so that the user's AP can connect to the Internet without authentication. To manage bandwidth, this research uses Hierarchical Token Bucket (HTB), which is a method of bandwidth management in Mikrotik that applies a hierarchical or tiered grouping concept. By combining these two methods, this research produces a good and appropriate RT RW Net Internet network. This provides access to information, business opportunities, healthcare services, education, and financial transactions online for rural communities. However, factors such as network infrastructure, trained human resources, and transparent and fair policies for all users need to be considered to run the RT RW Net business effectively and provide optimal benefits to the community.